Performance of ash gourd (benincasa hispida) in intercrop with different leafy vegetables (Progressive Agriculture, 2017)
Due to depletion of per capita land, consistent stress on improving factor productivity has warranted many alternative cropping strategies. The intercropping effect of red amaranth (Amaranthus gangeticus Linn, var. BARI Lalshak-1), jute leaf (Corchorus capsularis, var. Local) and stem amaranth (Amaranthus tricolor var. BARI Data-1) on the yield performance and thereby economic return of ash gourd as main crop was tested in low nitrogen and medium phosphorus and potassium under Netrakona district of Bangladesh. The experiment consisted of four crop combinations viz., sole ash gourd, ash gourd + red amaranth, ash gourd + jute leaf and ash gourd+ stem amaranth.Companion vegetables did not influence on the yield and yield parameters of ash gourd. Although, the highest yield was obtained from sole ash gourd (34.11 t ha-1)which was close to ash gourd + jute leaf (30.65 t ha-1) followed by ash gourd + red amaranth ( 29.34 t ha-1) intercrop combination. By intercropping of ash gourd with different vegetables, total productivity increased up to 6-16% over sole ash gourd due to the contribution of companion crops. The highest ash gourd equivalent yield (39.61 t ha-1) was recorded from ash gourd + stem amaranth combination. Ash gourd + stem amaranth combination gave the highest monetary returns in respect of gross return (Tk. 296880 ha-1) and gross margin (Tk. 174433 ha-1). The LER and ATER value for all the treatments were above one and this indicated that intercropping in ash gourd is biologically efficient. Considering the experimental findings, ash gourd + stem amaranth might be suitable combination for higher productivity and economic return.Progressive Agriculture 28 (2): 92-99, 2017